A study of diagnosis discrepancy between admission and discharge in Hospital Universiti Sains Malaysia - Adnan, Mohd Syafwan (2018)
Background: The accuracy of Emergency Department (ED) doctors in making a provisional diagnosis is crucial as it has direct impact on the patient treatment, safety, length of stay and cost of treatment. The study of the accuracy of the provisional diagnosis made by ED to compare with the discharge diagnosis is scarce in its availability and most results vary with different continents. This study was conducted to evaluate the accuracy of the diagnosis made by ED doctors in Hospital Universiti Sains Malaysia (HUSM) and the factors contributed to the discrepancy. Methods: This was a retrospective cross-sectional study in which medical records of patient admitted to hospital USM within Mei 2016 until December 2017 were selected using simple random sampling methods. The folders were then reviewed and the association within the categorized diagnosis accuracy was analysed using the ICD-10 classification. The sample size was 180 cases and cases was divided into two main categories. The factors associated with the unmatched diagnosis from both, patients and provider were then measured using multiple logistic regressions. Results: Hospital USM Emergency department had 84.4 percent of matched diagnosis with 15.56 percent of unmatched diagnosis. The odds of having unmatched diagnosis in patients from green zone are 4.2 times higher compared to the red zone. Conclusions: Hospital USM Emergency department had high diagnostic accuracy as compared to the unmatched diagnosis.